Plasma pentraxin-3 levels in patients with Takayasu's arteritis during routine follow-up - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2016)
Objective. To date, no biomarker is universally accepted to be a surrogate for active disease being one of major difficulties in follow-up of Takayasu's arteritis (TAK). In this study, we aimed to investigate plasma pentraxin-3 (PTX-3) levels and its correlation with activity in patients with TAK. Methods. This cross-sectional study included 94 patients (age: 43.3 +/- 13.6 years, F/M: 80/14) with TAK, 40 age-sex matched control donors (age: 41.5 +/- 9.3 years, F/M: 28/12). TAK patients were evaluated by physician's global assessment (PGA; active/inactive), as well as with the activity definition by Kerr et al. and with a new composite index of ITAS2010 (Indian Takayasu Clinical Activity Score). Plasma PTX-3 levels are measured with an enzyme linked immunosorbent assay kit. Results. Thirty-three (35.5%) patients were clinically active with PGA, while 25 (31.6%) patients and 28 (31.8%) patients were accepted to have active disease according to Kerr activity criteria and ITAS2010, respectively. Plasma PTX-3 levels were significantly higher in TAK patients compared to healthy controls (3.5 +/- 2.5 ng/ml vs. 2.5 +/- 1.6 ng/ml, p=0.029). However, PTX-3 levels were similar among active and inactive patients according to all three assessment tools. PTX-3 levels significantly correlated only with serum CRP levels. Conclusion. Although plasma PTX-3 levels were higher in patients with TAK compared to healthy controls, we observed no association with disease activity, limiting the role of PTX-3 level as a biomarker for active disease in TAK.
Keywords: Takayasu's arteritis; pentraxin-3; activity; DISEASE-ACTIVITY; DIAGNOSIS; PTX3; VASCULITIS